Corporatisation of Malaysian Public Universities: A Case Study - Ainun, Hj. Abd. Majid; Mohammad, Adam Bakar (2013)
This paper reports on a case study conducted in one of the Malaysian public universities to examine whether or not it is able to operate as a corporate entity as envisaged by the government. Specifically, it seeks to determine if the university is able to generate income equivalent to 30 per cent of its total expenditure by 2010, to assess how much its existing financial management systems contribute or hinders achievement of the target set and to offer explanation as to why current conditions came into being. Results showed that the target is not met, mainly due to limited avenues to generate fund internally and a rigid cost structure that did not allow much room for savings. Three reasons were offered as explanations as to why this situation existed.